Water Quality Monitoring and Controlling Using IoT - Johar, Haziq Lukman; Mohamad, Shamsul; Mohd Shah, Shaharil; Mohd Hanifa, Rafizah (Journal of Electronic Voltage and Application, 2021)
The water quality status of rivers in Malaysia has always been a cause for concern for various local authorities, government agencies, and the public. In the traditional method, the date has to be collected manually and for that reason, the workers must go to each tank or river to complete the task. The process set some drawbacks such as labor-intensive, high operational and equipment costs and lack of real-time data. In this research, the aim is to implement the Internet of Things (IoT) in monitoring and controlling the water quality. The pH and temperature sensors are integrated with NodeMCU ESP82666 to obtain the pH value and temperature data of the water. This platform is also used to control the servo motor to manage the systems. NodeMCU sends the data to the Internet via Blynk application. By using Blynk, users can monitor live data from the tank, see the data trend, and control the water quality. All the data that has been taken are saved in the Cloud database using phpMyAdmin. The connection also used NodeMCU ESP8266, where the coding is written and compiled using Arduino IDE software. This work has successfully achieved its objective where water quality data (pH and temperature) can be monitored, stored in a database, and controlled using IoT.